On-ice functional assessment of an elite ice hockey goaltender after treatment for femoroacetabular impingement - Tramer, J. S.; Deneweth, J. M.; Whiteside, D.; Ross, J. R.; Bedi, A.; Goulet, G. C. (Sports Health: A Multidisciplinary Approach, 2015)
Background: Femoroacetabular impingement (FAI) is a major cause of performance inhibition in elite-level athletes. The condition is characterized by pain, osseous abnormalities such as an increased alpha angle, and decreased range of motion at the affected hip joint. Arthroscopic surgical decompression is useful in reshaping the joint to alleviate symptoms. Functional kinematic outcomes of sport-specific movements after surgery, however, are presently unknown.